Competition for glucose between the yeasts Saccharomyces cerevisiae and Candida utilis. - Postma, E (1989)
The competition between the yeasts Saccharomyces cerevisiae CBS 8066 and Candida utilis CBS 621 for glucose was studied in sugar-limited chemostat cultures. Under aerobic conditions, C. utilis always successfully completed against S. cerevisiae. Only under anaerobic conditions did S. cerevisiae become the dominant species. The rationale behind these observations probably is that under aerobic glucose-limited conditions, high-affinity glucose/proton symporters are present in C. utilis, whereas in S. cerevisiae, glucose transport occurs via facilitated diffusion with low-affinity carriers. Our results explain the frequent occurrence of infections by Crabtree-negative yeasts during bakers' yeast production.